Calculation of the Planer Tool with a Glance of Physical Components of the Cutting Process Acting on Limited Contact Areas - Urinov Nasillo Fayzilloevich; Mukhammedov Mehriddin Beshimiovich (Zien Journals, 2022)
The article covers the designing of the planer tool considering the physical components of the cutting force acting on limited areas of chip contact and tool durability
Keywords: planer tool; 3D model; feeding; cutting modes